Dinâmica de queimadas em áreas úmidas protegidas e relações com fatores ambientais e antrópicos: o Parque Nacional de Ilha Grande (PR-MS) - Fragal, Everton Hafemann (2018)
The Ilha Grande National Park (IGNP) created in 1997 in the segment of floodplain in the Upper Parana River has gone burned area caused mainly by human activity. Proposed that park creation contribution to reduce burned areas, that is hypothesis must be test. The aim of this work was to analyze the dynamic of burned areas in the previous (1985 to 1997) and later (1998 to 2016) periods of the IGPN creation and relations with environmental and anthropic factors. For this, we integrated remote sensing data and products, hydrological data, environmental and anthropogenic data that provided: to verify the spatial and temporal relations to forest fires occurrences; to determinate the spectral index for detection of burned areas; to analyze the historical changes of dynamic of burned areas; and to establish the influence of environmental and anthropogenic factors in relation to burned areas frequency, added to model the probability of burns frequency in the park. Forest fires have relations with space and time. In the space, forest fires occurred in the herbaceous vegetation that has high flammability and near of access routes caused for ease fire ignition by the human activity. In the time, forest fires occurred mainly in August and September corresponded to smaller precipitation and lower levels of water of the Parana River in the year. The NBR index showed efficient to detect burned areas in the park, which applied to historical reconstruction of burned in the time series of this research. The changes in dynamics of burned areas revealed that after park creation intensified burned areas occurrences in central sector, meanwhile in the northern and southern sectors decreased burned areas. As the central sector of the park covers more than 50% of full area there was increase in burned areas occurrence after your creation in the time between 1998 and 2016. The environmental management of the park must get better to protect the natural resources, especially the vegetation. The environmental factors (hydroperiod and vertical distance to network drainage) and anthropic factors (land cover and access routes) respectively presented negative and positive influences in relation to occurrences of burns frequency in the park. The logistic regression model generated from the influences of these factors showed central sector of the park with high probability of burns frequency, which should be priority area for fire management. We conclude that the approach of this work assist to analyze dynamic of burned areas in the others wetlands and Conservation Units, which may contribute in knowledge to where and when about fires in protected environmental areas